Use of Naringinase to Modify the Sensory Quality of Foods and Increase the Bioavailability of Flavonoids: A Systematic Review - Joanna Bodakowska-Boczniewicz; Zbigniew Garncarek (Molecules)
As a complex of enzymes α-l-rhamnosidase and β-d-glucosidase, naringinase catalyzes the deglycosylation of flavonoids. According to the PRISMA method, a systematic literature review was conducted analyzing peer-reviewed scientific articles from the Scopus and Web of Science databases. Recent reviews on naringinase have focused on its sources, production, and general applications, whereas the present study highlights its specific applications, its role in the deglycosylation of flavonoids, and the resulting improvement in their bioavailability. This review focuses on advances in modifying the glycosidic parts of various flavonoids using naringinase by selectively disconnecting the rhamnose or glucose moiety. Removing rhamnose from the flavonoid molecule but leaving the glucose allows more water-soluble compounds to be present and increases bioavailability. A necessary condition for such selective deglycosylation is removing or inhibiting beta-glucosidase, the second enzyme in the native naringinase molecule. The use of naringinase for preparing functional beverages with increased antioxidant activity and for preparing steviol sweeteners is also presented. Naringinase enables the desired sensory properties to be obtained, primarily the taste and aroma of food products, and can be used in combination with other enzymes, e.g., pectinase and tannase.